Diagenetic geobodies: Fracture-controlled burial dolomite bodies in outcrops from Northern Oman - Vandeginste,V; John,CM; Beckert,J (Society of Petroleum Engineers International Petroleum Technology Conference 2014 Iptc 2014 Unlocking Energy Through Innovation Technology and Capability, 2014)
Diagenetic heterogeneities are difficult to predict in subsurface. Nevertheless, such heterogeneities can be crucial in hydrocarbon exploration. Diagenetic processes can significantly alter petrophysical properties of reservoir rocks, especially in carbonate rocks because of the reactive nature of the carbonate minerals. Dolomitization, i.e. the transformation of calcite (limestone) into dolomite, is a common diagenetic process in carbonate rocks. Description: an overview of the learning outcomes gained by studying fracture-related dolomite in outcrops of Oman and subsequent laboratory analysis over the last four years. A combined structural, petrographic and geochemical approach was taken to study three dolomite systems occurring in different stratigraphic host rock intervals. Application: Structurally-controlled dolomitization (i.e. dolomitization along faults and fractures) typically occurs in burial conditions, and the resulting strong permeability anisotropies caused by the dolomite textures can cause major challenges for hydrocarbon exploration. Results and Conclusions: Dolomite bodies in the Precambrian Khufai Formation are related to N-S to NNE-SSW fractures, whereas dolomite bodies that mainly occur in the Jurassic host rocks occur along reactivated WNW-ESE normal faults. These fracture-related dolomite bodies are generally less than 15 m wide, but can be up to a few hundred meters long. Late-diagenetic dolomite bodies were also recognized in Permian host rocks, where they occur at or close to the contact between Permian limestone and early-diagenetic dolomite. This late diagenetic dolomite system can be traced laterally for at least hundreds of meters and occurs in wadi's about 40 km apart. Our data indicate that there were several dolomitization events in the geological history, generating dolomite bodies with different characteristics. Technical Contributions: This highlights the needs to understand the timing and structural setting of dolomite bodies in